Understanding green building materials - Rider, Traci Rose. (W.W. Norton & Co., 2011)
Architects, Designers, And Contractors are increasingly familiar with the policies, procedures, and guidelines for achieving sustainable, or "green" building standards. But what about the green building materials themselves? What are they, what are the options, and how shuld you decide what to specify? --